Value Creation from Internationalization of Sugar Cane by-products: a multi-stakeholder view of artisanal cachaça production - Neutzling, Daiane Mulling; Santos, Manoela Silveira dos; Barcellos, Marcia Dutra de; Lauren Land, Anna (Review of Business Management, 2015)
Objective – The aim of this paper was to identify the strategies developed for internationalization in order to create value in the artisanal cachaça sector of Brazil. Design/methodology/approach – A multiple-case study was applied in two artisanal cachaçarias. we carried out in-depth, semi-structured interviews with different stakeholders involved in supporting internationalization of these companies. To select the stakeholders we used snowball sampling. The content of the interviews was categorized and analysed according to accepted theory. Findings – Our study provides an overview of the organization and structure of the cachaçarias and reveals how internationalization is adding value to this network from a multi-stakeholder view. The support of the multi-stakeholder network is in an early stage, but it offers a promising future, since there is a consumer market being developed. Political power is needed to regulate the industry. Practical implications – Business internationalization of the handmade cachaça sector is a challenge, as most companies are small and do not have adequate financial resources or proper knowledge regarding international markets. Regulatory stakeholders support the cachaçarias in standardizing production and developing international strategies. The results can help to better understand the importance of collaboration embedded in stakeholder network relationships. Originality/value – Empirical research on internationalization in developing countries, especially in small and mediums sized firms is still very limited. We have shown that companies can benefit from specific organization structures when developing relationships within multi-stakeholder networks.